Ritme dan Pola: Etnomatematika dalam Musik Jaipongan Jawa Barat - Helmy Wahyu Widiarti; Kusno Kusno (Mathematics Education Study Program, 2025)
This study aims to explore mathematical objects in music and traditional dance of Karawang, a region with rich cultural heritage in West Java. Traditional music and dance, such as Jaipongan and Ketuk Tilu, play an important role in preserving the cultural identity of the people of Karawang. In practice, mathematical elements such as rhythm, symmetry patterns, and repetition are visible in the structure of the music and dance movements of Jaipong. This research uses a qualitative approach through direct observation and in-depth interviews with local artists to understand the application of mathematical concepts in traditional cultural arts. The findings show that ethnomathematics naturally appears in these cultural forms, both implicitly and explicitly, and can be used as a medium for contextual and relevant mathematics learning.